GE_GERICHTE P/10607/2018 vom 7. Juli 2023 - GE Cour de justice (2023)
BRIGANDAGE;DISPOSITIONS PÉNALES DE LA LARM;DISPOSITIONS PÉNALES DE LA LSTUP;CONCOURS D'INFRACTIONS;PEINE PÉCUNIAIRE | CP.148a; LArm.33; LStup.19.al2; CP.140; CP.140; CP.140; LCR.95; CP.252; CP.251; CP.307; CP.147; CP.320; CP.146.al3; CP.49; CP.34